Synchronous Mucinous Tubular and Spindle Cell Carcinoma of the Kidney and Papillary Carcinoma of the Thyroid - Fernandes, Gwendolyn; Deshpande, Varsha Dipak; Choudhary, Sujata; Shinde, Swati (Annals of Pathology and Laboratory Medicine, 2020)
A 55 year old female, presented with flank pain and fullness since 2 years. On examination, a 10x10cm, ballotable lump was present in the right flank. CT Abdomen showed a 9.5x8.8 cm, exophytic mass lesion in the right kidney with patchy arterial enhancement and heterogenous enhancement in the venous phase. Whole body PET CT showed well defined, metabolically active masses in the right kidney, thyroid and cervical lymph nodes. Nephrectomy specimen received, showed a tumor measuring 12x7x6.5 cm creamy-white, fleshy, replacing the kidney. Histopathology revealed an unusual renal neoplasm with tubule formation merging with bland spindle cells and a focal myxoid stroma. Tumor cells were immunoreactive for CK7, EMA, vimentin and were negative for PAX8, CD10 & AMACR. The diagnosis of Mucinous Tubular and Spindle cell carcinoma (MTSCC) was established. FNAC of the thyroid nodules showed a classic papillary thyroid carcinoma.